2018
DOI: 10.1002/mp.12723
|View full text |Cite
|
Sign up to set email alerts
|

Proof of principle of helium‐beam radiography using silicon pixel detectors for energy deposition measurement, identification, and tracking of single ions

Abstract: A successful feasibility study of helium-beam radiography with the introduced detection system was conducted. The methodology of iRad was based on energy deposition measurements in thin silicon layers. The tracking of single ions and the method of the ion identification was shown to be important for helium-beam radiography in terms of spatial resolution and CNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
0
27
0
1
Order By: Relevance
“…While the investigations were so far mainly focused on the clinically available proton and carbon ion beams, recent studies have started addressing, both theoretically and experimentally, the potential of other ion beams being (re)considered for clinical introduction in the near future, particularly given the independence of the SPR needed for treatment planning on the imaging ion species. In this respect, helium ions are regarded as a very promising candidate, owing to their reduced lateral scattering compared to protons, and reduced imaging dose (at the same image quality) compared to carbon ions 3639 . In particular, Volz et al 38 confirmed experimentally almost a factor of two increased spatial resolution of 4 He ion radiography compared to proton radiography, as acquired with the same second generation prototype of refs.…”
Section: General Purpose Techniquesmentioning
confidence: 99%
“…While the investigations were so far mainly focused on the clinically available proton and carbon ion beams, recent studies have started addressing, both theoretically and experimentally, the potential of other ion beams being (re)considered for clinical introduction in the near future, particularly given the independence of the SPR needed for treatment planning on the imaging ion species. In this respect, helium ions are regarded as a very promising candidate, owing to their reduced lateral scattering compared to protons, and reduced imaging dose (at the same image quality) compared to carbon ions 3639 . In particular, Volz et al 38 confirmed experimentally almost a factor of two increased spatial resolution of 4 He ion radiography compared to proton radiography, as acquired with the same second generation prototype of refs.…”
Section: General Purpose Techniquesmentioning
confidence: 99%
“…Therefore, ion imaging requires sophisticated detector systems, capable of measuring particle track information and residual energy/range on a single-event basis (Schulte et al 2008). To date, several different prototype systems have been developed (Bashkirov et al 2009, Seco & Depauw 2011, Talamonti et al 2012, Uzunyan et al 2015, Bashkirov et al 2016a, Price 2016, Pettersen et al 2017, Gehrke et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, along with protons, heavier ions (mostly helium or carbon) have been considered for imaging given their smaller deviation due to multiple Coulomb scattering. The expected effect of an improved spatial resolution was observed, once the ion fragmentation was taken into account [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 90%